Caracterização populacional de melolonthidae do bioma Pampa e estrutura genética de Diloboderus abderus (sturm, 1826) - Valmorbida, Ivair (2017)
The natural grassland areas of the Pampa biome have been replaced by croplands for crop production, which can have impacts on the white grubs community. White grubs are known as the larval stage of Coleoptera from the family Melolonthidae, whose larvae are important component of soil macrofauna of agroecosystems, providing benefits due to gallery construction and nutrient cycling. Some species are root-feeding, such as the pasture white grub, Diloboderus abderus (Sturm, 1826). This species is one of the most important white grub pest in the Southern Cone of America. To characterize the Melolonthidae community, distribution, and population density, samples were performed in cultivated and natural grassland areas of 18 locations in the Brazilian Pampa. At each site, at least 25 trenches were open, larvae and adults were collected and identified. In the Brazilian Pampa, 1365 specimens were collected, belonging to 31 species, which four of them are pest species. Twenty two species were found in both landscape uses, three only in cultivated areas and seven only in natural grassland areas. D. abderus and Cyclocephala modesta were the most abundant and widely distributed in the Brazilian Pampa. Natural grassland areas had a greater abundance and diversity than cultivated areas. Our results demonstrate that exist a great diversity of white grubs in the Brazilian Pampa and that most species are capable of persisting in cultivated areas. Knowing species composition, population density, and how different species interact in agricultural areas are important to adopt management strategies. Larvae and adults of D. abderus were collected in the Southern Cone of America to perform the molecular characterization of this species. Specimens were identified, and the genomic DNA extracted from legs of larvae and adults. Subsequently, amplification of mitochondrial DNA cytochrome oxidade I (mtDNA COI), sequencing, trimming and alignment were performed. The sequencing of partial mtDNA COI of D. abderus allowed the identification of 19 haplotypes, high haplotype diversity and low nucleotide diversity. The haplotype Dabd01 was found in populations from Argentina, Paraguay, and Brazil. Low gene flow was observed among populations of D. abderus in the Southern Cone of America, but the populations are not geographically isolated.